2022
DOI: 10.3390/ani12091194
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-Omics Analysis Revealed a Metabolic Regulatory System of Cecum in Rabbit with Diarrhea

Abstract: With the comprehensive prohibition of antibiotics in the feed industry in China, the incidence of diarrhea in rabbits increased, such as loss of appetite, vomiting, and excretion of atheromatous feces. In order to explore the pathological and the molecular mechanisms of the diarrhea in the rabbitry fed with antibiotic-free diet, we used microbial metagenomics, transcriptome, and non-targeted metabolomics sequencing. The results showed that the Firmicutes level was significantly decreased (p < 0.001) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Fournierella and Anaerosporobacter have been reported to be significantly associated with intrahepatic fat accumulation ( Yaskolka Meir et al, 2021 ). Fournierella might be involved in bile secretion and tryptophan metabolism in rabbits with diarrhea ( Wang et al, 2022 ). Anaerosporobacter may cause vascular damage and worsen renal function in murine models ( Li et al, 2020 ) and was reported to be associated with an increase in trimethylamine oxide (TMAO) content in vivo ( Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fournierella and Anaerosporobacter have been reported to be significantly associated with intrahepatic fat accumulation ( Yaskolka Meir et al, 2021 ). Fournierella might be involved in bile secretion and tryptophan metabolism in rabbits with diarrhea ( Wang et al, 2022 ). Anaerosporobacter may cause vascular damage and worsen renal function in murine models ( Li et al, 2020 ) and was reported to be associated with an increase in trimethylamine oxide (TMAO) content in vivo ( Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased Helicobacter due to Salmonella infection was not restored by phage treatment. The major genus Fournierella in the phage treatment group, newly discovered in recent years, has been shown to be positively correlated with myricetin and ursolic acid in the cecum of diarrhea-afflicted rabbits; its increase might cause bile secretion and tryptophan metabolism disorders and aggravate intestinal inflammation, thus leading to diarrhea in rabbits ( Wang et al, 2022 ). We thus hypothesized that the failure of phage treatment to restore the weight loss of Salmonella -infected chicks might be likely related to the still disturbed gut flora, mainly including increased abundance of Fournierella, Escherichia-Shigella , and Helicobacter species.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proven in ruminants that excessive organic acids can lead to the occurrence of rumen acidosis, and in this study, we also found that a high NFC ratio can lead to a decrease in the pH of the cecum. Decreasing the dietary NDF can increase the concentration of VFA in the cecum of rabbits, decrease the pH of the cecum, and improve the fermentation pattern of the cecum (Wu et al, 2019 ; Wang et al, 2022a ). Therefore, it is considered that the lower the NFC/NDF in the diet, the higher the fiber contents in the diet, the less the fermentable substances, and the poorer the ability of intestinal fermentation to produce acids, resulting in an increase in the pH of the cecum.…”
Section: Discussionmentioning
confidence: 99%